Inclusive Learning Apps: Exploring Experiences Disabilities in Digital Learning - Topo Yono; Fitrotul Mufaridah (Universitas Negeri Jakarta Postgraduate of Physical Education Departments, 2026)
The use of appropriate learning media technology plays a crucial role in fostering students’ character development. This study aims to explore the potential implementation of digital storytelling as a learning medium to build and strengthen independent character among students in special schools (SLB). Independent character is essential as it encompasses students’ ability to make decisions, take responsibility, and demonstrate initiative autonomously. This research employs a qualitative approach, with data collected through observations and interviews. The participants consisted of 22 students from SLB Harapan Pelangi Kalisat. Data were analyzed systematically through the stages of data reduction, data display, and conclusion drawing/verification. The findings indicate that the use of digital storytelling based on independent character values is both effective and innovative, with an implementation rate reaching 98%. This approach provides meaningful learning experiences for students with disabilities, enabling them to better understand and internalize the values of independence in the learning process.